SYNERGETIC CHARACTER OF ARCHITECTURAL ELEMENTS OF TRANSPORTAION NETWORKS OF INDUSTRIAL AREAS - Lyamzin, Andrey; Khara, Marina; Marintseva, Kristina (Proceedings of National Aviation University (archive), 2016)
The objective: Stability of the flow processes in industrial areas directly depends upon the degree of synergetic character of the elements, that make up the architecture of their transpiration networks. The bulk of specialists consider railway and automobile transportation networks to be transportation thoroughfares with static architecture only, although, primarily, they are but a series of structural and functional elements, acting according to synergetic principles, typical of industrial regions, having an essential impact both on environmental safety and supporting their functioning. In many industrial areas transportation networks also represent historical monuments to architectural and engineering ideas. Territories, located along transportation networks possess a substantial town-planning, architectural, historical and cultural potential. All aforementioned confirms the necessity of compiling a mechanism of evaluation of functionality of the existing architecture of transportation networks of industrial areas (hereinafter ATNIA), based on the principle of synergetic. The principles: The proposed mechanism of evaluation of functionality of ATNIA elements, characterize as synergetic is based upon an electric-dynamic model of control over transportation flows and was named on the analogy with gravitational model, in which bodies’ masses correspond to the zones of arrivals and departures, while the distance between zones to transportation expenses. The results: The operational hypothesis, regarding the fact that a transportation network of an industrial area represents a combinatorial space and can be evaluated by means of different methods of electrical engineering, according to Kirchoff’s laws proved to be true. Owing to development of electrodynamic, giving an evaluation of behaviour of transportation flows within boundaries of transportation networks in industrial areas there appeared an opportunity of determining the level of functionality of the latter. The novelty of research: appears due to development of an electrodynamic model on the basis of the main principles of synergetic, which determine functionality of ATNIA methods. The practical value: Application of theoretical issues, taken from electrostatics, the branch of physics makes it possible not only to give a quantitative evaluation of transportation flows, within the boundaries of combinatorial space of transportation network of industrial areas, but also evaluate ATNIA functionality.